Novel composite clinical endpoints and risk scores used in clinical trials in pulmonary arterial hypertension. (November 2020) - Sitbon, Olivier; Nikkho, Sylvia; Benza, Raymond; (CQ) Deng, Chunqin; Farber, Harrison W.; Gomberg-Maitland, Mardi; Hassoun, Paul; Meier, Christian; Pepke-Zaba, Joanna; Prasad, Krishna; Seeger, Werner; Corris, Paul A
This manuscript on endpoints incorporates the broad experience of members of Pulmonary Vascular Research Institute's Innovative Drug Development Initiative as an open debate platform for academia, the pharmaceutical industry and regulatory experts surrounding the future design of clinical trials in pulmonary hypertension. It reviews our current understanding of endpoints used in phase 2 and 3 trials for pulmonary hypertension and discusses in detail the value of newer approaches. These include the roles of composite endpoints and how these can be developed and validated. The newer concept of risk analysis is also discussed, including how such risk scores might be utilised as endpoints in clinical trials.